(2x-6)+(60-x)=22

Simple and best practice solution for (2x-6)+(60-x)=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-6)+(60-x)=22 equation:



(2x-6)+(60-x)=22
We move all terms to the left:
(2x-6)+(60-x)-(22)=0
We add all the numbers together, and all the variables
(2x-6)+(-1x+60)-22=0
We get rid of parentheses
2x-1x-6+60-22=0
We add all the numbers together, and all the variables
x+32=0
We move all terms containing x to the left, all other terms to the right
x=-32

See similar equations:

| 25-5x=-5 | | n+140=336 | | 0.25/0.5=1.5/x | | 5p-2=3(p-4) | | 30k+1=18k+22 | | 4m2-4m-3=0 | | 15x+6x=84 | | 3+7x=-5x+75 | | -16x2+128x+96=0 | | 2/1y+5/2=42/5 | | 2/1y+2/5=42/5 | | 12a+12=2a-78 | | ⅔(9y-15)=14 | | 3^5x=4 | | 4x+3=5x-7=7-66 | | n+22=50 | | 40=4n*2 | | 5/2y+3/6=53/6 | | 33-6b+5b=30 | | 4x^2-8x-15=3 | | 5(4y+21)=851 | | 1/4r+6=12 | | 3^5z=4 | | (6x+2)+2x=180 | | 3(6n-8)=48 | | 8.1x-2.2=38.8 | | 1.5=x*500.00 | | 2x-7=5x-61=x+11 | | 2^x÷2^-4=45 | | 3p2+9p-3p-9=0 | | 57+2x=117 | | x=x=x=2 |

Equations solver categories